1990
DOI: 10.1002/jcla.1860040510
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to viral antigens, xenoantigens, and autoantigens in alzheimer's disease

Abstract: Sera from 19 patients with Alzheimer's disease (AD) and 21 control subjects were studied by immunofluorescence and enzyme immunoassay for antibody activity against various viruses and 12 self- and non-self-antigens. Total IgG mean level was significantly higher in the AD group; the IgG level was above 15 g/L in 52.8% of AD patients versus 14.3% of control subjects. Antiviral antibody titers showed no significant differences except for antibodies to herpes simplex virus-1, which were increased in control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 56 publications
2
29
1
Order By: Relevance
“…In contrast, subjects with positive detection of anti-HSV IgG antibodies in the sera were not at higher risk of AD than IgG-negative subjects. This last result is in accordance with previous case-control clinical series [10], [11]. These results were confirmed when analysing the evolution of cognitive performance measured by the MMSE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, subjects with positive detection of anti-HSV IgG antibodies in the sera were not at higher risk of AD than IgG-negative subjects. This last result is in accordance with previous case-control clinical series [10], [11]. These results were confirmed when analysing the evolution of cognitive performance measured by the MMSE.…”
Section: Discussionsupporting
confidence: 92%
“…Renvoize et al [10] found no statistically significant difference in serum antibody titres to HSV in a sample of 33 AD patients and 28 controls. Ounanian et al [11] in a sample of 19 AD patients and 21 controls, showed increased titres of antibodies to HSV in the control group but the proportion of HSV-positive subjects was not different between AD and control groups. These studies were performed on small samples of individuals and with IgG antibodies only, which characterise past infections.…”
Section: Introductionmentioning
confidence: 93%
“…Pathologically, immune system components (Abs, complement, and T cells (9)) have been detected in the brains of AD patients. Recently, patients with AD were found to manifest T cell reactivity to amyloid-␤ peptide (10) and Abs to glial fibrillary acidic protein (GFAP) (11) and to other selected autoantigens (12). Other studies have detected Abs against uncharacterized Ag(s) in the choroid plexus (13), Abs to microglial cells (14), and Abs to myelin basic protein (15).…”
Section: Identification Of Aldolase As a Target Antigen In Alzheimer'mentioning
confidence: 99%
“…However, AD patients have been found to have not only high titers of autoantibodies directed to non-brain antigens (antibodies to thyroglobulin and thyroid microsomal antigen, anti-nuclear antibodies, antibodies to smooth muscle, mitochondria and gastric parietal cell), often found in aged controls (Watts, 1985;McRae-Degueurce, Haglid, Rosengren, Wallin, Blennow, Gottfries and Dahlstrom, 1988;Ounanian, Gilbert, Renversez, Seigneurin and Avrameas, 1990;Lopez, Rabin and Huff, 1991;Genovesi, Paolini, Marcellini, Vernillo, Salvati, Polidori, Ricciardi, de Nuccio and Re, 1996), but also anti-brain autoantibodies (Singh and Fudenberg, 1986;Schott, Wormstall, Dietrich, Klein and Batra, 1996;Loeffler, Juneau, Nguyen, Najman, Pomara and LeWitt, 1997;Singh, 1997 Haglid, Rosengren, Karlsson, Karlsson, Wallin, Svennerholm, Gottfries and Dahlstrom, 1987;Singh and Fudenberg, 1989).…”
Section: Humoral Immunitymentioning
confidence: 99%